Evaluation of impurity densities from charge exchange recombination spectroscopy measurements at ASDEX Upgrade. (26th July 2018) - McDermott, R M; Dux, R; Pütterich, T; Geiger, B; Kappatou, A; Lebschy, A; Bruhn, C; Cavedon, M; Frank, A; Harder, N den; Viezzer, E
Abstract: At ASDEX upgrade (AUG) a new framework for the evaluation of impurity densities based on measurements from charge exchange recombination spectroscopy (CXRS) diagnostics has been developed. The charge exchange impurity concentration analysis code, or CHICA, can perform these calculations for all of the beam-based CXRS diagnostics at AUG and is equipped with the atomic data for all of the regularly measured charge exchange spectral lines (He, Li, B, C, N, O, and Ne). CHICA includes four different methods for the evaluation of the neutral density populations, which feature different implementations and contain varying levels of sophistication. These methods have been thoroughly benchmarked against one another, enabling the important processes for the evaluation of neutral densities to be identified as well as the neutral populations that are most critical to the accurate interpretation of the measured CXRS intensities. For the AUG neutral beams, charge exchange with the ground state of the first energy component is typically the dominant contribution to the measured CXRS intensities, but emission from reactions with the n  = 2 beam halo population can contribute up to 35% to the total signal and must be included in the analysis. Neglect of this population leads to incorrect magnitudes and incorrect profile shapes of the calculated impurity density profiles. The edge lines of sight (LOS) of the core CXRS diagnostics at AUG intersect the edge pedestal inside of the neutral beam volume. Therefore, the impurity density is not constant along the LOS, complicating the interpretation of the measured intensities. Within CHICA a forward model for the edge impurity densities has been implemented, enabling the reconstruction of accurate edge profiles.